Optimalisasi Penggunaan Buku Teks dalam Upaya Meningkatkan Prestasi Belajar di SMP - Kulsum, Dewi Umi (Universitas Muhammadiyah Surakarta, 2015)
This research aim to description about usage of textbook in the effort increasing achievement of matter learning Travelling at educative participant of class VIII B State of Junior High School two Cawas Region Klaten even semester of school year 2014/2015. Subject and research data source is 22 students. Data collecting method applies observation, documentation, and test. Data analysis applies critical analysis and comparability. Indicator success of using minimal limit criteria 75 and complete target of100%. Research procedure applies cycle. Result of inferential research and solution: From continuation data of enclosure 5, yard, data obtained from finite precycle of cycle II, obtained progress of achievement of student learning in study of English with matter Travelling, at precycle average of 76,1 and cycle I average of 78,7 and cycle II average of89,8 Of data is, seems to explain that happened increase of average of value from precycleto cycle I 2,6 numbers (3,4%), from cycle I to cycle II happened increase 11,2 numbers (10,8%), from pasiklus to cycle II happened increase 12,1 numbers (16,8%). Highest value of phase precycle 82 and cycle I 84 and cycle II 96. Seems to explain that from phase precycle to cycle I happened increase equal to 2 number (2,4%), from cycle I to cycle II happened increase 12 numbers (14,2%), and from precycle to cycle II happened increase13,8 numbers (18,1%). Low value of phase precycle is obtained by 68 and cycle I 74 andcycle II 84. thereby, can be affirmed that from phase precycle to cycle I happened increase equal to 6 number (8,8%), from cycle I to cycle II happened increase 10 numbers (13,5%), and from precycle to cycle II happened increase 16 numbers (24%). Complete percentage learnt starts from precycle is obtained equal to 64% and cycle I is obtained equal to 90% and cycle II equal to 100%. Seems to explain that from phase precycle to cycle I happened increase equal to 26%, from cycle I to cycle II happened increase equal to 10%, and from precycle to cycle II happened increase equal to 36%. Thereby, achievement of student learning in study of English with matter Travelling from finite precycle of cycle II happened increase significant.